Improving eye screening practice among pediatric rheumatology patients receiving hydroxychloroquine. (February 2021) - AlAhmed, Ohoud; Way, Amanda; Akoghlanian, Shoghik; Barbar-Smiley, Fatima; Lemle, Stephanie; MacDonald, Darby; Frost, Emily; Wise, Kelly; Lee, Lindsey; Ardoin, Stacy P; Sivaraman, Vidya
Objective: Hydroxychloroquine (HCQ) is commonly used in the treatment of various autoimmune diseases related to its many benefits and favorable safety profile. Although HCQ retinopathy was considered to be uncommon, a prevalence of 7.5% was described in a recent study making early detection critical. The most updated screening guidelines by the American Academy of Ophthalmology were published in 2016; however, it lacked pediatric-specific recommendations and the overall compliance with screening guidelines was poor in previous studies. We developed a quality improvement (QI) initiative aiming to create institutional screening recommendations. Additionally, to increase eye screening in pediatric rheumatology clinic for patients receiving HCQ from 65% to 85% in 12 months and to sustain that rate for at least 6 months. Methods: We formed a multidisciplinary team of pediatric rheumatologists and ophthalmologists, clinical pharmacist, clinic nurses, QI specialist, quality data technician and administrative staff. We included patients receiving HCQ and who were evaluated at Nationwide Children's Hospital rheumatology clinic. A key driver diagram was formulated to identify barriers to compliance and determine possible interventions. Main interventions included summarizing screening guidelines in a step by step algorithm, increasing awareness of these guidelines among patients and providers, improving collaboration and communication with ophthalmologists, and initiating pre-visit planning. Results: Baseline performance data included 164 patients. Fifty-four (33%) of those patients were at high risk for HCQ retinopathy. Of them, 50% were on HCQ dose of >5 mg/kg/day and 31.5% had been taking HCQ for ≥5 years. Two center line shifts were noticed over the course of the project. The target of 85% compliance was reached in February 2019 and was sustained until December 2019. Conclusions: Our study highlights the importance of interdisciplinary communication to increase awareness of screening guidelines among medical providers and patients. Pre-visit planning played a major role in identifying patients and opportunities for optimizing eye screening in patients at risk for HCQ retinopathy. Collaboration between rheumatologists and ophthalmologists is crucial in managing patients on HCQ. The implementation of same-day eye screening allowed this collaboration to be more efficient. Future efforts are being directed at monitoring and improving utilization of the effective interventions.